Biomimetic Beetle-Inspired Flapping Air Vehicle Actuated by Ionic Polymer-Metal Composite Actuator - Zhao, Yang (Appl Bionics Biomech, 2018)
During the last decades, the ionic polymer-metal composite (IPMC) received much attention because of its potential capabilities, such as large displacement and flexible bending actuation. In this paper, a biomimetic flapping air vehicle was proposed by combining the superiority of ionic polymer metal composite with the bionic beetle flapping principle. The blocking force was compared between casted IPMC and IPMC. The flapping state of the wing was investigated and the maximum displacement and flapping angle were measured. The flapping displacement under different voltage and frequency was tested. The flapping displacement of the wing and the support reaction force were measured under different frequency by experiments. The experimental results indicate that the high voltage and low frequency would get large flapping displacement.